Inhibition of CRAC with a human anti-ORAI1 monoclonal antibody inhibits T-cell-derived cytokine production but fails to inhibit a T-cell-dependent antibody response in the cynomolgus monkey. (April 2015) - Gaida, Kevin; Salimi-Moosavi, Hossein; Subramanian, Raju; Almon, Valerie; Knize, Anna; Zhang, Ming; Lin, Fen-Fen; Nguyen, Hung Q.; Zhou, Lei; Sullivan, John K.; Wong, Min; McBride, Helen J.
Abstract ORAI1 is the pore-forming component of calcium release-activated calcium (CRAC) channels. CRAC channels are the primary route for calcium ion (Ca2+) entry into T-cells following antigen stimulation. This Ca2+ entry induces proliferation and cytokine production through activation of calcineurin and the nuclear factor of activated T-cells (NFAT) transcription factor along with subsequent cytokine-related genes. It was hypothesized that the in vivo inhibition of T-cell function by blocking ORAI1 or calcineurin would lead to similar functional consequences. To test this hypothesis the activity of 2C1.1, a fully human anti-ORAI1 monoclonal antibody, and cyclosporin A (CsA) were tested in vivo for their suppressive effect on T-cell-derived cytokine production and a T-cell-dependent antibody response (TDAR) using sheep red blood cells (SRBC) in cynomolgus monkeys. Despite showing similar inhibition of ex vivo interleukin (IL)-2 production by stimulated T-cells, both molecules exhibited different pharmacologic effects on the SRBC antibody response. CsA blocked the development of SRBC-specific antibodies, while 2C1.1 failed to inhibit the antigen-specific antibody response. These surprising observations suggest that full inhibition of the CRAC channel is required to inhibit a functional immune response, consistent with findings from human patients with loss of function mutations in ORAI1.